Adults Behaving Badly: The Effects of Own and Peer Parents' Incarceration on Adolescent Criminal Activities - Jason M. Fletcher (Institute of Labor Economics (IZA), 2017)
A maturing literature across the social sciences suggests important impacts of the intergenerational transmission of crime as well as peer effects that determine youth criminal activities. This paper explores these channels by examining gender-specific effects of maternal and paternal incarceration from both own-parents and classmate-parents. This paper also adds to the literature by exploiting across-cohort, within school exposure to peer parent incarceration to enhance causal inference. While the intergenerational correlations of criminal activities are similar by gender (father-son/mother-son), the results suggest that peer parent incarceration transmits effects largely along gender lines, which is suggestive of specific learning mechanisms. Peer maternal incarceration increases adolescent female criminal activities and reduces male crime and the reverse is true for peer paternal incarceration. These effects are strongest for youth reports of selling drugs and engaging in physical violence. In contrast, the effects of peer parental incarceration on other outcomes, such as GPA, do not vary by gender.
Keywords: J00; J24; J62; 330; intergenerational transmission; peer effects; crime